'The rollercoaster': A qualitative study of midwifery students' experiences affecting their mental wellbeing. (September 2020) - Oates, Jennifer; Topping, Alice; Watts, Kim; Charles, Penny; Hunter, Caroline; Arias, Teresa
Highlights: Student midwives' experience of pre-registration training may be described as 'a rollercoaster' of emotional fluctuation and relentless change. Students were aware of the importance of emotion management and self care as part of professional socialisation but were not confident regarding how to develop such skills. Student midwives value opportunities for individual support from midwifery educators and regular opportunities to connect with their peers. Abstract: Objective: Midwifery student mental wellbeing is an important consideration for the sustainability of the profession, however it has seldom been the subject of empirical research. Previous studies of the lived experience of midwifery students have focused on the impact of transition experiences and student satisfaction, rather than specifically on mental health and students' views on support for their mental wellbeing. Design: A qualitative descriptive study using semi-structured interviews. Setting: A midwifery undergraduate programme in one university in the South of England. Participants: 20 BSc midwifery students. Findings: Two inductive themes were developed from our analysis. The theme of 'the rollercoaster' encapsulated students' experience over the length of the course, characterised by multiple culture shocks of being in different worlds, from one clinical placement to the next, from university to clinical placement. This experience was emotionally taxing. The theme of 'being noticed, feeling connected' encapsulated midwifery students' views on what could help them enjoy their training. They wanted to be seen as individuals by at least one educator, they wanted opportunities to connect with their peers and they wanted the support available to them to be consistent. Conclusions: Listening to students' insights into the lived experience of being a midwifery student can enable midwifery educators to improve the way courses are designed and support structures are put in place. The importance of having consistent contact with peers and educators cannot be underestimated. Implications for practice: The emotional demands of midwifery training must be acknowledged. Educators should identify ways in which they can provide students with consistent individualised support and regular opportunities to meet with their peers.